Lyophilization to enable distribution of ChAdOx1 and ChAdOx2 adenovirus-vectored vaccines without refrigeration - Zhang, C; Berg, A; Joe, C; Dalby, PA; Douglas, A (Springer Nature, 2023)
Distribution of vaccines which require refrigerated or frozen storage can be challenging and expensive. The adenovirus vector platform has been widely used for COVID-19 vaccines while several further candidate vaccines using the platform are in clinical development. In current liquid formulations, adenoviruses require distribution at 2–8 °C. The development of formulations suitable for ambient temperature distribution would be advantageous. Previous peer-reviewed reports of adenovirus lyophilization are relatively limited. Here, we report the development of a formulation and process for lyophilization of simian adenovirus-vectored vaccines based on the ChAdOx1 platform. We describe the iterative selection of excipients using a design of experiments approach, and iterative cycle improvement to achieve both preservation of potency and satisfactory cake appearance. The resulting method achieved in-process infectivity titre loss of around 50%. After drying, there was negligible further loss over a month at 30 °C. Around 30% of the predrying infectivity remained after a month at 45 °C. This performance is likely to be suitable for ‘last leg’ distribution at ambient temperature. This work may also facilitate the development of other product presentations using dried simian adenovirus-vectored vaccines.